Managing burnout in the workplace a guide for information professionals - McCormack, Nancy; Cotter, Catherine (Catherine Anne) (Chandos information professional series, 2013)
Nancy McCormack is Head of the Lederman Law Library and Associate Professor of Law at Queen's University, Canada.Catherine Cotter is Reference/Instruction Librarian at the University of New Brunswick, Canada. She is responsible for reference and instruction services for law library patrons and teaching the legal research component of the first year Fundamentals of Advocacy course